To exempt or not to exempt non-accelerated filers from compliance with the auditor attestation requirement of Section 404(b) of the Sarbanes–Oxley Act. Issue 2 (October 2016) - Brown, Kareen E.; Elayan, Fayez A.; Li, Jingyu; Mohammad, Emad; Pacharn, Parunchana; Liu, Zhefeng Frank
Abstract: We examine the stock market reaction to the SEC announcement to permanently exempt non-accelerated filers from compliance with Section 404(b) of the Sarbanes–Oxley Act. Mandatory compliance with auditor attestation under Section 404(b) is highly controversial. Using a sample of non-accelerated issuers for 2006–2011, we find a negative market reaction to the November 4, 2009 exemption announcement. However, most of the negative returns accrue to non-accelerated filers that do not voluntarily comply with Section 404(b), suggesting that auditor attestation enhances firm value. The use of a Big 4 auditor, strong analyst following, and superior internal controls over financial reporting (ICFR) are associated with positive/less negative market responses. Voluntary compliers with Section 404(b) are more likely to have a Big 4 auditor, stronger analyst coverage, effective ICFR, stronger firm performance and lower information asymmetry. Our results are consistent with firms using voluntary compliance with SOX 404(b) as a signal of superior operating performance and ICFR quality to overcome information asymmetry and therefore mitigate the negative valuation impact of the permanent exemption from auditor attestation.